Eotaxin in serum of patients with asthma or chronic obstructive pulmonary disease: relationship with eosinophil cationic protein and lung function - Karina Jahnz-Ró̀zyk; Tadeusz Plusa; Justyna Mierzejewska (Mediators of Inflammation)
This study was undertaken to investigate the correlation between the serum ECP and the serum eotaxin level, and disease activity as evaluated with pulmonary function in patients with asthma or chronic obstructive pulmonary disease (COPD). 20 patients with stable asthma and 15 patients with COPD, and 15 subjects of the control group took part in this study. The analysis of ECP was performed according to the manufacturer’s directions (Pharmacia Diagnostics AB, Uppsala, Sweden). The ELISA test was used to measure eotaxin levels in sserum (kits from R&D, USA). The levels of ECP were 16.9 ± 6.3 μg/L in patients with asthma, 15.1 ± 9.3 μg/L in patients with COPD and 11.8 ± 6.2 μg/L in the control group (p<0.05). There was no significant difference in the asthma ECP level compared with the ECP level in COPD. There was a significant difference between the ECP plasma level in asthma compared with the ECP plasma level in the control group (p<0.05). The levels of eotaxin were 175.8 ± 49.3 pg/mL in the control group. There was a correlation of ECP and the eotaxin level in asthma patients (r=+0.5,p<0.05). The percentage fall in FEV1 correlated with eotaxin level in asthma (r=−0.3,p<0.05) and with the eotaxin level in COPD (r=−0.05,p<0.05). Serum outcomes of eotaxin and ECP levels appear to be a useful indicator of atopic asthma, and might provide complementary data disease monitoring. Therefore, further investigations are required to clarify whether serum eotaxin measurements have a role in the clinical evaluation in COPD.